Sacred subdivisions: the postsuburban transformation of American evangelicalism - Wilford, Justin G. (New York University Press, 2012)
Introduction -- Sacred archipelgaos: spaces of secularization -- Sacred scenes: postsuburbia and evangelical performance -- Purpose driven pluralities: variety, consumption and choice in postdenominational evangelicalism -- Purpose driven places: small performances in big churches -- Purpose driven planet: the globalization of evangelical postsuburbia -- Purpose driven politics: the saddleback civil forum and the new civility of evangelism -- Conclusion: assembling spaces of fusion, de-fusion, and diffusion in the postsuburban landscape